Genome‐Wide Population Structure in a Marine Keystone Species, the European Flat Oyster ( Ostrea edulis ) - Homère J. Alves Monteiro; Dorte Bekkevold; George Pacheco; Stein Mortensen; Runyang Nicolas Lou; Nina O. Therkildsen; Arnaud Tanguy; Chloé Robert; Pierre De Wit; Dorte Meldrup; Ane T. Laugen; Philine S. E. zu Ermgassen; et al. (Molecular Ecology, 2025)
Ostrea edulis, the European flat oyster, was once a widespread economically and ecologically important marine species, but has suffered dramatic declines over the past two centuries. Consequently, there has been a surge in European restoration efforts, many of which focus on restocking as a conservation measure. In this study, we used whole‐genome sequencing (WGS) data to investigate the population structure, demographic history, and patterns of local adaptation of O. edulis across its natural distribution with increased sampling densities at Scandinavian localities. Results revealed seven distinct genetic clusters, including previously undescribed complex population structure in Norway, and evidence for introgression between genetic clusters in Scandinavia. We detected large structural variants (SVs) on three pseudo‐chromosomes. These megabase long regions were characterised by strong linkage disequilibrium and clear geographical differentiation, suggestive of chromosomal inversions potentially associated with local adaptation. The results indicated that genomic traces of past translocations of non‐native O. edulis were still present in some individuals, but overall, we found limited evidence of major impacts of translocations on the scale of contemporary population structure. Our findings highlight the importance of considering population structure and signatures of selection in the design of effective conservation strategies to preserve and restore wild native European flat oyster populations, and we provide direct knowledge safeguarding sustainable mitigation actions in this important species.